Principles and practice of sport management - Masteralexis, Lisa P.; Barr, Carol A.;Hums, Mary A. (Sudbury, Massachusetts : Jone and Bartlett Learning, 2012)
From the basic knowledge and skill sets of a sport manager to current trends and issues in the sport management industry, Principles and Practice of Sport Management, Fourth Edition provides the foundation for students as they study and prepare for a variety of sport management careers. The editors and chapter contributors, all well-known sport industry professionals, show students how to apply their new knowledge
1. History of sport management -- 2. Management principles applied to sport management -- 3. Marketing principles applied to sport management -- 4. Financial and economic principles applied to sport management -- 5. Legal principles applied to sport management -- 6. Ethical principles applied to sport management -- 7. High school and youth sports -- 8. Collegiate sport -- 9. International sport -- 10. Professional sport -- 11. Sports agency -- 12. Facility management -- 13. Event management -- 14. Sport sales -- 15. Sport sponsorship -- 16. Sport communications -- 17. Sport broadcasting -- 18. Sport and new media -- 19. The sporting goods and licensed products industries -- 20. Golf and club management -- 21. Recreational sport -- 22. Strategies for career success.
Includes index.
Keywords: SPORTS ADMINISTRATION